Tren Penelitian Layanan Perpustakaan Melalui Pemanfaatan Repositori Institusi dengan Analisis Bibliometrik Berbasis Data Scopus - Faridan, Ridwan; Lawanda, Ike Iswary (Media Informasi, 2024)
This research aims to determine research trends in library services through the use of institutional repositories. This research was conducted in April 2024 by searching through the Scopus database with the keywords library services and institutional repositories. The search result data was processed and analyzed descriptively using the VOSViewer application to determine the bibliometric map of this research. The research results show that the development of library service research through the use of institutional repositories with bibliometric analysis indexed by Scopus from 1982 to 2023 has increased significantly but fluctuated. The journal that most publishes this research is OCLC Systems And Services. The most productive researcher writing this research was Joachim Schöpfel. The institution that publishes the most research is the University of Illinois Urbana-Champaign. The most country that publishes this research is the United States. The most common type of document from this research is in the form of articles. The dominant field is Social Sciences. Through network visualization, relationships between scientific concepts and 9 clusters can be identified. The density and network visualization shows that in the development of this research there are still opportunities for further research.